Javanese Lexical Configuration - ANDRIANY, L. (Utopía y Praxis Latinoamericana, 2020)
ABSTRACT This research aims to look at the lexical configuration model in Javanese. The research method is descriptive qualitative research, with data sources obtained from the conversation of the Javanese user community in the city of Yogyakarta and Solo in Central Java province. The results showed that the Javanese lexical configuration of the hierarchical structure consisted of transitive dominance relation, asymmetric domination relation, and symmetrical dominance relation. The analysis also shows that Javanese has a taxonomic branching hierarchy and a merging branching hierarchy. In addition to the taxonomic branchless hierarchy configuration, a branchless hierarchy configuration and proposal session configuration are also found.